Perancangan Arsitektur Electronic Medical Record (EMR) menggunakan Metode Enterprise Architecture Planning (EAP) Arsitektur Enterprise - Seni Meilani Putri; Umi Hayati; Rizal Dzulkarnaen (Journal of Information Technology, 2020)
Sonny Medika Bidan Enen Clinic is a health service provider that has skilled medical personnel, but data management at the clinic is still done manually. The risk of errors in storing and managing medical record data caused by human error is still quite high, so that it can reduce the quality of service. With the design of the EMR (Electronic Medical Record) system it can help the process of managing medical record data, so that service and archive storage is better and can reduce errors that occur. The design of the EMR is done by the EAP (Enterprise Architecture Planning) method using the Zachman Framework. There are four stages carried out which include the seven main components of EAP, namely Design Initiation, Business Modeling, Current Technology Systems, Data Architecture Design, Application Architecture design, Technology Architecture Design, and Implementation Plan. The results of the EMR design by the EAP method successfully defined 3 business processes. In the data architecture produces 7 data entities, in the application architecture 4 application proposals are generated, and in the technology architecture the proposed architectural technology design is generated .